Influence of water regime on grape aromatic composition of Muscat of Alexandria in a semiarid climate - Buesa, Ignacio; Intrigliolo, Diego S.; Castel, Juan R.; Vilanova, Mar (Elsevier, 2021)
Irrigation effects in relation to the environmental conditions on grape aromas are still unknown. This study aims to clarify the effects of water regime on the aromatic composition of “Muscat of Alexandria” grapes under the semiarid climate conditions of eastern Spain and over three seasons. The relationships between total volatile composition in free and glycosidically-bound fractions, vine performance, and grape composition were also assessed. The watering treatments studied were: sustained deficit irrigation (SDI) at 50% of the estimated crop evapotranspiration (ETc); early deficit (EDI), where pre-veraison water deficit was imposed; late deficit (LDI), in which a water shortage was applied during post-veraison; and control (C), irrigated at 100% of ETc during the entire season. The effects of water regimes on volatile and glycosidically-bound composition were different between seasons due to the predominant effect of the environmental conditions on aromatic composition. The seasons with the greater yield were associated to a lower grape aromatic composition, however, this effect at the crop level was less pronounced in the most irrigated treatment. In drier seasons, irrigation delayed ripening and increased the terpene concentration of “Muscat of Alexandria” grapes, showing a high treatment and season interaction. Specific water regimes have the potential to buffer the effects of environmental conditions on the aromatic composition of “Muscat of Alexandria” grapes in a semi-arid climate, as the result of the complex relationships between climatic factors, vine performance and grape maturity.